The Developmental Of Social Studies By Using Inquiry Model In Sdi Kardina Massa Blitar - Hadi Mustofa (Journal of Development Research, 2017)
The observation results of Social studies process in Islamic Elementary School Blitar city are founded many problems. They are: (1) Social studies is not interesting, (2) the study is not meaningful for the students, (3) the students feel bored with the study, (4) the concepts which are presented to the students are separately, (5) the study is limited to read a book or hear an explanation, and (6) the result score of social studies is low. Based on those problems above, so it needs a study model exchange which more interesting than before. One of the study models which can be done is social study which has an inquiry. This research uses developmental model which is done by many steps: (1) introduction study, (2) developmental model, (3) test model. The results of this research are shown that Social studies by using inquiry study model is effective and efficient to increace the student competence for getting knowledge, attitude, and skills as the goals of the study. In particular, attitude and skills which are mastered by the student are scientific attitude and skills.